Jadomycin breast cancer cytotoxicity is mediated by a copper‐dependent, reactive oxygen species–inducing mechanism. Issue 2 (2nd February 2015) - Hall, Steven R.; Blundon, Heather L.; Ladda, Matthew A.; Robertson, Andrew W.; Martinez‐Farina, Camilo F.; Jakeman, David L.; Goralski, Kerry B.
Abstract: Jadomycins are natural products biosynthesized by the bacteria Streptomyces venezuelae which kill drug‐sensitive and multidrug‐resistant breast cancer cells in culture. Currently, the mechanisms of jadomycin cytotoxicity are poorly understood; however, reactive oxygen species (ROS)–induced DNA cleavage is suggested based on bacterial plasmid DNA cleavage studies. The objective of this study was to determine if and how ROS contribute to jadomycin cytotoxicity in drug‐sensitive MCF7 (MCF7‐CON) and taxol‐resistant MCF7 (MCF7‐TXL) breast cancer cells. As determined using an intracellular, fluorescent, ROS‐detecting probe, jadomycins B, S, SPhG, and F dose dependently increased intracellular ROS activity 2.5‐ to 5.9‐fold. Cotreatment with the antioxidant N ‐acetyl cysteine lowered ROS concentrations to below baseline levels and decreased the corresponding cytotoxic potency of the four jadomycins 1.9‐ to 3.3‐fold, confirming a ROS‐mediated mechanism. Addition of CuSO4 enhanced, whereas addition of the Cu(II)‐chelatord ‐penicillamine reduced, the ROS generation and cytotoxicity of each jadomycin. Specific inhibitors of the antioxidant enzymes, superoxide dismutase 1, glutathione S ‐transferase, and thioredoxin reductase, but not catalase, enhanced jadomycin‐mediated ROS generation and anticancer activity. In conclusion, the results indicate that jadomycin cytotoxicity involves the generation of cytosolic superoxide via a Cu(II)‐jadomycin reaction, a mechanism common to all jadomycins tested and observed in MCF7‐CON and drug‐resistant MCF7‐TXL cells. The superoxide dismutase 1, glutathione, and peroxiredoxin/thioredoxin cellular antioxidant enzyme pathways scavenged intracellular ROS generated by jadomycin treatment. Blocking these antioxidant pathways could serve as a strategy to enhance jadomycin cytotoxic potency in drug‐sensitive and multidrug‐resistant breast cancers. Abstract : e00110